BEDAH RUMAH: KOMODIFIKASI KEMISKINAN DAN BUDAYA KONSUMSI - Widodo, Anhar (Capture : Jurnal Seni Media Rekam, 2010)
This paper will review the co relation between poverty who becomes the object, the media that is doing commodification, and consumption as the goal of the commodification of the object by the media. Television program Bedah Rumah is very helpful in realizing the government’s program a simple home for the poor. This is not explain that government programs are not fully successful, proven there are still those who can not afford to get their basic rights, particularly employment and decent living.Keyword: Television program, poor, consumption